2021
DOI: 10.3310/hsdr09150
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis for health services and policy: case studies in the scoping of reviews

Abstract: Background For systematic reviews to be rigorous, deliverable and useful, they need a well-defined review question. Scoping for a review also requires the specification of clear inclusion criteria and planned synthesis methods. Guidance is lacking on how to develop these, especially in the context of undertaking rapid and responsive systematic reviews to inform health services and health policy. Objective This report describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Useful insights about and examples of evidence synthesis in health and social care research have been set out in a report from the NIHR Evidence Synthesis Centres. 94 Evidence reviews can be integrated into different stages of rapid evaluations, often being used to inform a scoping exercise by mapping the available published research evidence in relation to the wider context or prior implementation of a similar intervention. These reviews can also help researchers understand how these interventions have been evaluated in the past and use these insights to inform the rapid evaluation scope and design.…”
Section: Rapid Evidence Reviewsmentioning
confidence: 99%
“…Useful insights about and examples of evidence synthesis in health and social care research have been set out in a report from the NIHR Evidence Synthesis Centres. 94 Evidence reviews can be integrated into different stages of rapid evaluations, often being used to inform a scoping exercise by mapping the available published research evidence in relation to the wider context or prior implementation of a similar intervention. These reviews can also help researchers understand how these interventions have been evaluated in the past and use these insights to inform the rapid evaluation scope and design.…”
Section: Rapid Evidence Reviewsmentioning
confidence: 99%
“…It is one of three review facilities, commissioned on a 3-year renewable contract to conduct literature reviews within time-sensitive windows, to inform both policy and future research (Chambers, Booth, et al, 2021). Future topics are discussed at an annual performance review meeting with members of the NIHR HS&DR Programme team or, subsequently, surface as urgent priorities throughout the rest of the year (Anderson et al, 2021). Review products range from desk based surveys of ongoing research, concluded within three or four working days, to full-scale systematic reviews where multiple reviewers are employed to accelerate the review process.…”
Section: The Context For Our Investigationmentioning
confidence: 99%